Phenomenon-Based Learning, Filozofia i Design-Thinking, czyli pomysł na kształcenie myślenia i metodę łączenia treści nauczania w polskim systemie edukacji - Czujko-Moszyk, Ewelina (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
This article offers an authorial idea of curriculum contents integration thanks to implementation of phenomenon-based learning method, philosophy as a school subject, and design thinking. Author believes that teaching contents and school subjects need to be integrated in order to comprehensively discuss modern phenomena in lessons. The manuscript presents briefly each component: Finnish phenomenon-based learning method and its circumstances of implementation, design thinking and an example of its application to education, as well as philosophy as a school subject to teach thinking and as a supplement for phenomenonbased learning method. The article attempts to prove that these components have certain objectives and characteristics in common and they complete one another providing new quality of teaching. This proposal is specifically designed for Polish education system having in consideration its obstacles and opportunities. Nevertheless, this idea might act also as an inspiration for other countries because it is meant to be universal.